Ronald L. Meek (comp.). Marx, Engels y la explosión demográfica, México, Editorial Extemporáneos, 1973. 248 p. - Hernández Millán, Abelardo (Estudios Demográficos y Urbanos, 1974)
Ronald L. Meek (Comp.) Marx, Engels y la explosión demográfica, México, Editorial Extemporáneos, 1973.